Non-symmetrical fatigue life of nodular graphite cast iron under non-proportional multi-axial cyclic loading. (August 2019) - Kachit, M.; Courbon, J.; Boulnat, X.; Adrien, J.; Verdu, C.
Highlights: There was a reduction of fatigue life when the phase shift evolute from 0° or 180–90°. Nonsymmetric behavior of both fatigue life and crack distribution relatively to δ = 90°. More planes undergoing a tensile cracks mode for δ < 90° than for δ > 90° loads. Abstract: Non-proportional axial-torsional loading fatigue tests on nodular cast iron revealed a non-symmetrical behavior of the fatigue life relatively to the phase shift angle δ = 90° between axial and torsion loads. This behavior was in agreement with fatigue crack orientation investigated using optical and electron microscopy. Elasto-plastic finite element model (FEM) were used to assess the crack orientation behavior and it could explain this non-symmetrical behavior by the non-symmetrical values of both σI and σI / σII ratio relatively to δ = 90°. FEM revealed that for the δ < 90° loads, principal stress was applied essentially at critical planes of low angle ϕn, thus occurrence of tensile cracks mode was higher for δ < 90° than for δ > 90° load, which reduces the fatigue life. σI / σII ratio strongly influenced the dominant crack mode. When the applied loads were torsion σI /σII = 1, cracks were observed to occur, equally, in modes I and II. Presence of the non-propagating failure (mode II) significantly increased the fatigue life. Conversely, for high phase shift, where σI / σII ≫ 1, crack mode I dominated and crack driving force remained high during the whole fatigue cycle, inducing a lower fatigue limit.